A fogalmi metaforák szerepe a bűn fogalom konceptualizációja során - Lechner Ilona; Ilona Lekhner; Лехнер Ілона (Видавництво МДУ, 2019)
A tanulmány részletesen foglalkozik a konceptualizációs folyamattal, a nyelv, a gondolkodás, valamint a kultúra összefüggéseivel. Bemutatja a fogalmi metafora-elmélet legfőbb jellemzőit, illetve kihangsúlyozza annak fontos szerepét a konceptualizáció során. Az elmélet szerint elvont fogalmakat konkrét fogalmak segítségével érthetünk meg. Ezt a folyamatot a ’bűn’ fogalom példáján mutatja be számos példát sorakoztatva fel.

Резюме. У статті детально розглянуто процес концептуалізації, показано зв’язок між контекстом мови, мисленням та культурою. Описано основні риси концептуальної теорії метафори і підкреслено її важливу роль у концептуалізації. Згідно з теорією, абстрактні поняття можна зрозуміти за допомогою конкретних понять. Цей процес ілюструється прикладами поняття «гріх».

Abstract. The study deals in detail with the conceptualization process, the connection of the language, thinking and culture. A concept only has meaning to us if we have any experience with it. The conceptualisation of a concept can occur in our minds as a result of various cognitive processes, most of which can be traced back to our physical experiences. All of this contributes to the success of the interpretation of objects / events / concepts in our physical, social and cultural environment, that is, the creation of the meaning. These cognitive mechanisms, of course, do not function consciously and without them it would be impossible for us to interpret the entities of the world around us. The aim of conceptual processes is to help us build up our conceptual system and interpret new experiences to expand and change it. The study presents the main features of conceptual metaphor theory and emphasizes its important role in conceptualization. In the traditional sense, metaphors are categorized as poetic images and interpreted by literary writers. The function of metaphors is thus to achieve an artistic or rhetorical effect. According to the followers of cognitive language theory, the main task of the discipline is to describe the metaphor of natural language, since the conceptual metaphor is one of the basic tools of the conceptualization process. The study focuses on the parts of conceptual metaphors, the basics and types of metaphors, and the levels of metaphor research. One of the main statements of the theory is that abstract concepts can be understood by means of concrete concepts. This process is illustrated by the example of the term "sin". It demonstrates what cognitive model can develop in our minds and what specific concepts are involved in this process.
Роль когнітивних метафор в концептуалізації концепту «гріх»
Role of cognitive metaphors in conceptualization of the concept «sin»
https://pp-msu.com.ua/uk/article/rol-kognitivnikh-metafor-v-kontseptualizatsiyi-kontseptu-grikh
Keywords: konceptualizáció; fogalmi metafora; fogalmi metafora-elmélet; elvont fogalmak; концептуалізація; концептуальна метафора; теорія концептуальної метафори; абстрактне поняття; conceptualization; conceptual metaphor; conceptual metaphor theory; abstract concepts